A Fruitful Two Way Relationship: Arthur Miller and Irish Theatre - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2023)
The essay investigates the mutual relationship between Miller and Irish theatre life under a title that takes its cue from Two Way Mirror, attempting to highlight the number of ways in which the two sides, mirror-like, reflect on each other. I believe that considering them together may illuminate certain, not so obvious aspects or components of both while suggesting new paths for research